History of the Moluccan's Cloves as a Global Commodity - Hatib Abdul Kadir (Kawalu: Journal of Local Culture, 2018)
Abstract This paper focuses on the history of spice trade in Moluccas. Using two main approaches of firstly, Braudel, I intend to examine the histoty of spice trade in Moluccas in the 16th century in relation with the changing of the structure of economy that affected the social and political relations of the Moluccans. Secondly, applying Wallerstein approaches, I find out that trading activities from the 16th century until today have created a wide gap between post-colonial Moluccas and the Europeans. To conclude, I argue that economic activities have always been accompanied by forcing political power, such as monopoly and military power. Consequently, they have created unequal relations between the state and society